High-speed data provision via mobile networks in Latin America and the Caribbean. Issue 4 (12th June 2017) - Curwen, Peter; Whalley, Jason
Abstract : Purpose: The purpose of this paper is to examine in a fully up-to-date manner the position in respect of the licensing and launch of long-term evolution (LTE) (4G) in a region that attracts relatively little attention in academic work and the media. The purpose is also to examine the role of incumbency and to assess to what extent the licensing of LTE can make a difference to the structure of mobile markets in the region. Design/methodology/approach: The first step has been to compile extensive databases with respect to the licensing and launch of high-speed networks in the region, arranged so as to emphasize the position of the dominant incumbents. A distinction is drawn between the larger, mainly Latin American, countries and the smaller, mainly Caribbean, islands. There is a discussion of new entry and its potential to disrupt incumbents. Findings: The position of dominance held by two operators – América Móvil and Telefonica in the larger countries and by Digicel and Cable & Wireless Communications (Liberty Global) in the islands – is brought to the fore, and the analysis demonstrates that this is unlikely to be more than marginally affected by regulatory attempts to restructure markets by, for example, fostering new entry. Research limitations/implications: This is necessarily an overview paper as more than 50 countries/islands are covered, so detailed individual country studies are precluded. Practical implications: The way forward, such as it is, can only be illuminated by first clarifying the current state of play. Originality/value: The databases that underpin the analysis are author-compiled and entirely original.